State Bar Media Conference at Fresno Hilton Hotel - Watkins, Howard::::::::: (1984)
Media workshop: on left middle: State Bar President Burke Critchfield; on right, reporter Carol Corey, Judge Robert Coyle and ? Carol Corey became an attorney in 1987